Process simulation-based improvements to maximize naphtha production in an existing gas processing plant (2016)
The parameters for the proper operation of each one of the process stages (compression, cooling, and separation) in an existing gas processing plant which processes 1.5 million standard cubic feet per day (MMSCFD) were determined. The gas plant was simulated using the Aspen HYSYS® V7.3 software with the current operational plant conditions and the measured properties of the fluids (gas chromatography for input gas, fuel gas, and LPG). Subsequently, unidimensional searches were performed via sensitivity analyses of the key stages of the process to obtain suitable parameters for improving naphtha production. This resulted in a maximum naphtha recovery rate of 99.13% (which is an improvement over the current recovery rate of 82.79%) and an increase in naphtha quality of 20.85%. This approach provides a tool for decision-making and establishes a basis for analyzing other plants